Sulfated Polysaccharides in the Freshwater Green Macroalga Cladophora surera Not Linked to Salinity Adaptation - Arata, Paula X.; Alberghina, Josefina; Confalonieri, Viviana; Errea, María I.; Estevez, José M.; Ciancia, Marina (Frontiers in Plant Science, 2017)
The presence of sulfated polysaccharides in cell walls of seaweeds is considered to be a consequence of the physiological adaptation to the high salinity of the marine environment. Recently, it was found that sulfated polysaccharides were present in certain freshwater Cladophora species and some vascular plants. Cladophora (Ulvophyceae, Chlorophyta) is one of the largest genera of green algae that are able to grow in both, seas and freshwater courses. Previous studies carried out on the water-soluble polysaccharides of the marine species C. falklandica established the presence of sulfated xylogalactoarabinans constituted by a backbone of 4-linked -L-arabinopyranose units partially sulfated mainly on C3 and also on C2 with partial glycosylation, mostly on C2, with terminal -D-xylopyranose or -D-galactofuranose units. Besides, minor amounts of 3-, 6- and/or 3,6-linked -D-galactan structures, with galactose in the pyranosic form were detected. In this work, the main water soluble cell wall polysaccharides from the freshwater alga Cladophora surera were characterized. It was found that this green alga biosynthesizes sulfated polysaccharides, with a structure similar to those found in marine species of this genus. Calibration of molecular clock with fossil data suggests that colonization of freshwater environments occurred during the Miocene by its ancestor. Therefore, the presence of sulfated polysaccharides in the freshwater green macroalga C. surera could be, in this case, an adaptation to transient desiccation and changes in ionic strength. Retention of sulfated polysaccharides at the cell walls may represent a snapshot of an evolutionary event, and, thus constitutes an excellent model for further studies on the mechanisms of sulfation on cell wall polysaccharides and environmental stress co-evolution.